Kaji Eksperimental Alat Pengering Tenaga Surya Aktif Pemanasan Langsung (Direct Solar Dryer Active) Berbentuk Jajar Genjang Tipe Kabinet - Suprayitno Suprayitno; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The direct solar drying model of the parallelogram cabinet type is a dryer of parallelogram shaped, which is intended to produce a uniform temperature distribution, so that the drying results can be uniformly and faster. This research aims to conduct an experimental study of direct solar drying, type of cabinet parallelogram shaped. The dried material was bananas, a drying capacity of 8 kg. Data obtained from this research was the temperature, radiation intensity, and mass reduction in bananas. Based on the data obtained, the average temperature in the drying chamber was 35.18ºC to 59.56ºC. The highest temperature of 62ºC occurred in racks 8 and the lowest temperature of 34ºC occurred in rack 1. The highest mass reduction was 0.301 kg occurred in racks 8 and the lowest mass reduction was 0.237 kg occurred in the first rack. Based on data, the higher of temperature, the mass reduction in the banana would be faster.Keywords: Solar Dryer, Mass Reduction, Drying